Mesh partitioning for distributed systems - Jian Chen; Taylor, V. (Proceedings, the seventh International Symposium on High Performance Distributed Computing (Cat. No.98TB100244) : 31 July 1998, 1998)
Distributed systems, which consist of a collection of high performance systems interconnected via high performance networks (e.g. ATM), are becoming feasible platforms for execution of large-scale, complex problems. We address various issues related to mesh partitioning for distributed systems. These issues include the metric used to compare different partitions, efficiency of the application executing on a distributed system, the number of cut sets, and the advantage of exploiting heterogeneity in network performance. We present a tool called PART for automatic mesh partitioning for distributed systems. The novel feature of PART is that it considers heterogeneities in the application and the distributed system. The heterogeneities in the distributed system include processor and network performance; the heterogeneities in the application include computational complexities. Preliminary results are presented for partitioning regular and irregular finite element meshes for the WHAMS2D application executing on a distributed system consisting of two IBM SPs. The results from the regular problems indicate a 33-46% increase in efficiency when processor performance is considered as compared to the conventional even partitioning; the results also indicate an additional 5-16% increase in efficiency when network performance is considered. The result from the irregular problem indicate a 21% increase in efficiency when processor and network performance are considered as compared to even partitioning.